Generative AI Ethno-Digital Comics Enhancing Socio-Cultural Awareness and Value-Based Learning in Elementary Education - Teguh Ardianto; Nandang Kusmana; Sobri Sobri; Yusup Junaedi; Andri Imam Subekhi (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aimed to develop and evaluate an AI-assisted ethno-digital comic using AI Comic Factory to improve elementary students’ cultural literacy, character development, and learning engagement in culturally responsive learning contexts. Methodology: This study employed a Design-Based Research (DBR) approach involving analysis, design, and evaluation phases. Participants consisted of 60 elementary students from Grades IV–VI and 12 students in a preliminary trial from two schools in Banten, Indonesia. Data were collected through expert validation, questionnaires, observations, and field testing, then analyzed using Aiken’s V, Cronbach’s Alpha, ICC, N-gain, and Cohen’s d. Main Findings: The developed comic demonstrated high validity (Aiken’s V = 0.88–0.94) and strong reliability (α = 0.89). Field implementation showed significant improvement in students’ socio-cultural awareness (N-gain = 0.70; Cohen’s d = 2.02), character development (d = 1.77), and learning engagement (M = 4.34; ICC = 0.89). Emotional and reflective engagement showed greater improvement than behavioral and cognitive engagement. In addition, Technology Acceptance Model (TAM) results indicated very high user acceptance, particularly in behavioral intention (BI = 4.58) and perceived usefulness (PU = 4.52). Novelty/Originality of this study: This study proposes an AI-assisted ethno-digital story-based learning model integrating generative AI, culturally responsive pedagogy, and DBR to support immersive cultural storytelling and measurable character-based learning outcomes in elementary education.